2018
DOI: 10.1071/wr17056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding conflict and consensus regarding wood bison management in Alaska, USA

Abstract: Context Wood bison (Bison bison athabascae) have been absent from Alaska for over 170 years. In the spring and summer of 2015, however, 130 animals were reintroduced to the state. These wood bison were restored through a consensus-based planning process, but it remains unknown how the animals will be managed. Aims To survey urban and rural Alaska residents to understand the effect of proximity to the resource on residents’ preferences for management of wood bison in different scenarios. Methods Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Currently, increasing attention is paid to the impact of people’s views on wildlife management as well as the fact that the survival of many endangered species depends on the willingness of communities to coexist with them [ 36 , 39 , 40 , 41 , 42 , 43 ]. In this paper we showed that this problem is also very important for the conservation of free-living populations of European bison in the mountainous landscape of Bieszczady.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, increasing attention is paid to the impact of people’s views on wildlife management as well as the fact that the survival of many endangered species depends on the willingness of communities to coexist with them [ 36 , 39 , 40 , 41 , 42 , 43 ]. In this paper we showed that this problem is also very important for the conservation of free-living populations of European bison in the mountainous landscape of Bieszczady.…”
Section: Discussionmentioning
confidence: 99%
“…In this study area, the positive effects of many years of conservation activities and the growth of the European bison population are clearly visible [ 3 ]. As suggested in previous studies, however, the growing population of this large herbivore is causing an increase in the number of conflict situations, thus threatening a decrease in local communities’ willingness to coexist with them [ 34 , 35 , 36 ]. We have shown that human dimensions in the management of European bison in Bieszczady are multifaceted and require greater effective integration of natural and social sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the attitudes of rural landowners may have far-reaching implications for ponds, they are rarely examined outside of the context of human-wildlife conflicts (e.g., [30,31]) or consumption/utilitarianism [32]. Rural decision-making is also influenced by stewardship values [33,34], and it is clear that rural residents value both tangible (i.e., economic) and intangible (i.e., cultural, intrinsic, or aesthetic) benefits provided by wildlife [35].…”
Section: The Importance Of Wildlife Values and Attitudes For Managementmentioning
confidence: 99%
“…Linear features have received considerable attention in the context of caribou conservation; however, other species may respond differently to LFs, including "threatened" wood bison (Bison bison athabascae Rhoads, 1898). Effects of LFs on wood bison are not well understood, and the few studies to date have been equivocal, with some suggesting that LFs improve habitat suitability by increasing forage availability (Mitchell and Gates 2002;Leverkus 2015) and others suggesting that they may be detrimental because they increase bison-human conflict (Thiessen 2009;Jung 2017;Doney et al 2018;Jung and Larter 2018) and increase hunting pressure (Environment and Climate Change Canada 2018b). Such effects may not be mutually exclusive and their relative importance on bison behaviour and demography may be context-dependent.…”
Section: Introductionmentioning
confidence: 99%